PERTIMBANGAN PUTUSAN HAKIM TERHADAP PELAKU TINDAK PIDANA MENTRANSMISIKAN BERITA BOHONG YANG MENGAKIBATKAN KERUGIAN KONSUMEN (SOL JUSTICIA, 2023)
One of the crimes that occur in the field of information and electronic transactions is transmitting fake news which results in consumer losses, as happened in Decision Number: 453/Pid.Sus/2022/PN.Tjk. The problem of this research is: How is the judge's decision considered against the perpetrators of the crime of transmitting fake news which results in consumer losses and how is the accountability of the perpetrators of criminal acts transmitting fake news which results in consumer losses. This research uses normative juridical and empirical juridical approaches. Data collection was carried out by library research and field studies. The data were then analyzed qualitatively. The results of the study show that the considerations of the judge's decision imposing prison sentences and fines on the perpetrators of the crime of transmitting fake news which result in consumer losses consist of juridical, philosophical and sociological considerations. Juridical considerations, namely the actions of the defendant are proven to have violated Article 45A Paragraph (1) Jo. Article 28 Paragraph (1) of the ITE Law. Philosophical considerations, namely the judge considers that the imposition of a sentence is not only aimed at causing a deterrent effect but as an effort to punish the defendant. Sociological considerations, namely the judge considers things that are aggravating and mitigating punishment for the defendant. The responsibility of the perpetrators of the crime of transmitting fake news which results in consumer losses is based on the ability of the perpetrators to be responsible, the presence of mistakes and absence of excuses and justifications for criminal.